Cardiopulmonary cerebral resuscitation in the case of out-of-hospital cardiac arrest witnessed by emergency medical team: A case study - Đurđević Ljijana (ABC: časopis urgentne medicine, 2015)
INTODUCTION: Cardiopulmonary cerebral resuscitation (CPCR) represents clearly defined procedures and administration of definite medicines with the purpose of enabling the person with cardiac arrest to oxygenate the tissue, reestablish spontaneous circulation and perform restitution of cerebral function and other vital systems of the organism. The cardiac arrest is a a sudden and unexpected stop in blood circulation caused by the functional loss of heart operation - the cessation of the heart mechanical activity, and inability to pump enough blood to maintain adequate perfusion and nourishment of the brain. AIM: Present CPCR measures taken prehospitally at the scene of event, and the necessity of a timely and adequate CPCR inititation. Determine prehospital survival of patients for whom emergency medical service (EMS) teams take CPCR measures when a sudden cardiac arrest occurs in the presence of emergency medical service (EMS) team. MATERIALS AND METHODS: A descriptive overview of data, dispatcher's Protocol, Physician's Protocol and ERC Guidelines from 2010, Patient's Discharge Note. CASE REPORT: At 7:03 a.m. the dispatcher received a call reporting that a 73 year old female had lost consciousness. Within two minutes, the team set out for the scene in accordance with the first degree of urgency protocol. After four minutes the team arrived at the reported address. The son gave the information that the patient had lost consciousness for a short time but that she was feeling well at the moment. The patient was found conscious, oriented, eupnoic, in the sitting position on the bed. On examination, normal breath sounds were observed, sinus bradychardia of 40 beats per minute and BP 160/80mmHg. During preparation for ECG recording, a pulse oxymetry was performed, which showed 93% SaO2. At that moment, the patient lost consciousness, stopped breathing, and the pulse was not palpable any more. She was positioned in the lying position, with the help of other team members, and an external heart massage was started. A venous pathway was established. VF was displayed on the defibrillator monitor. The patient was defibrillated using a biphasic defibrillator with a 200J energy level. A tachyarrhythmia of about 100/min was displayed on the monitor. On insertion of laryngoscope in order to establish an airway she made one spontanous respiration. She continued to breathe spontaneously at about 10 respirations/sec. A pulse was palpated over the carotids. Measures were taken for an urgent transport to the Admission Ward of Valjevo Hospital. In the transport vehicle, 500 ml 0.9% NaCl solution and 8l/min oxygen via mask were included. The patient regained consciousness during the transport. She was admitted with stable vital parameters to the Coronary Unit of Valjevo Hospital. CONCLUSION: In order to achieve CPCR efficacy it is necessary to initiate resuscitation measures in the shortest possible time from the moment of cardiac arrest occurrence so that the cerebral functions and other vital systems of the organism could be preserved.